Observations of glories above arctic boundary layer clouds to identify cloud phase - Kanngießer, Franz; Ehrlich, André; Wendisch, Manfred (Universität Leipzig, 2017)
The glory is an optical phenomenon observed above liquid water clouds and consists of coloured rings around the anti-solar point. Since the glory is caused by scattering on spherical particles it can be used as a proxy to identify liquid water at the cloud top. Images taken with a CANON digital camera equipped with a fish-eye lens on board the research aircraft Polar 5 during the measurement campaign Radiation-Aerosol-Cloud Experiment in the Arctic Circle (RACEPAC) were analysed for glories. To identify glories an algorithm consisting of five criteria was developed by using simulations of the scattering angle dependent radiance and a test data set of measurements. The algorithm was tested and proved to be able to distinguish between images showing a glory and images not showing any glory. Die Glorie ist eine optische Erscheinung, die über Flüssigwasserwolken beobachtet werden kann und aus farbigen Ringen um den Gegensonnenpunkt besteht. Da die Glorie durch Streuung an sphärischen Partikeln entsteht, kann sie zur Identifikation von Flüssigwasser am Wolkenoberrand genutzt werden. Bilder, die mit einer CANON Digitalkamera, die mit einem Fischaugenobjektiv ausgestattet war, von Bord des Forschungsflugzeugs Polar 5 während der Messkampagne RACEPAC aufgenommen worden, wurden auf das Auftreten von Glorien untersucht. Zur Identifikation wurde ein Algorithmus mit fünf Kriterien entwickelt, die mit Hilfe von Simulationen der streuwinkelabhängigen Radianz und einem Testdatensatz der Messungen erstellt wurden. Der Algorithmus wurde getestet und ist in der Lage zwischen Bildern mit und ohne Glorie zu unterscheiden.